If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4y-3/7=3
We move all terms to the left:
4y-3/7-(3)=0
determiningTheFunctionDomain 4y-3-3/7=0
We multiply all the terms by the denominator
4y*7-3-3*7=0
We add all the numbers together, and all the variables
4y*7-24=0
Wy multiply elements
28y-24=0
We move all terms containing y to the left, all other terms to the right
28y=24
y=24/28
y=6/7
| -9+6z=6-9z | | 27y/28-7=1-4y/7 | | 5a-80=70 | | 6-9p=-5p-9-9 | | 3k+2=41 | | 2x^{2}+6x-20=0 | | -h+6=-2h+10 | | 29.2/8=x/4 | | 3x+26=5x-20 | | p-6/14=-1 | | -17=19n=-150 | | 17=-3(23-m)+2(m-2) | | -2+m/9=-3 | | 6i-3=-18+i | | p+7/3=7 | | -8x-18=-274 | | 47=31-4(x-2) | | p+6/3=3 | | 16x+19=595 | | x-5/6=-1/6 | | n=9/10=-4 | | p–5=-2 | | 22=2h+10 | | -4.5+3=2-8.5x | | B.2/3b-1/3b=4/3 | | 39=26-b | | 7l-4=2l+16 | | -66=-3(m+5) | | 15=-5t^2+20t+1 | | 4(-x+2)=x-5+3 | | 5b+5=14+2b | | -3/7h=42 |